The Impact of the Building Forms of Tall Buildings on Dust Accumulation and Thermal Performance in Hot Climates - Emad S. Mushtaha; Tareq Salameh; Deena Al Qurneh; Sahar Hassan; Rawan Hamad; Mohammad Ali Abdelkareem; Abdul Hai Al-Alami; Abdul Ghani Olabi; Taro Mori (Buildings, 2022)
This study aims to create an iconic dust-control skyscraper that resembles an environmentally friendly structure, by adapting a new dust simulation design approach. This method seeks to reduce dust dispersion in the air, control dust movement, and siphon it from the ambient air to purify the surrounding environment by implementing design techniques in the skyscrapers of the UAE. To tackle this critical but often overlooked issue, this study focuses on building typologies along the Sheikh Zayed road region in Dubai city due to the area’s importance and the existence of numerous renowned skyscrapers. An analytical study was conducted to categorize the typologies, followed by a performance analysis to assess the impact of accumulated dust on solar radiation and the overall thermal performance of the structures. Fourteen cases were evaluated using ANSYS simulation software selected for their basic typologies and their possible existence in reality. The study’s design guidelines were set according to the results conducted from running the simulation, as the findings suggested that wind streamlines may easily travel around a circular-shaped structure, while a building’s sharp edges act as wind barriers, driving the wind away from the structure and allowing dust to collect on the surfaces. The ideal example, according to the study’s conclusions, was the trapezoid form (case 14), which was established by simulation results that demonstrated a 3.4% reduction in roof conduction and a 1.3% reduction in yearly cooling. On the other hand, a biomimetic design approach was also integrated into the study to devise a design concept that effectively responds to nature. Preliminary ideas and potential future avenues for this project are also discussed.